Anticancer Potential of Three Sea Cucumber Species Extracts on Human Breast Cancer Cell Line - Rameshkumar Santhanam; Nurul Shahirah Mohd Azam; Ammira Shafiqha Abdul Khadar; Ambrose Louise; Gregory Dominic; Nur Shahida Ahmad Sofian; See Wee Han; Thiruventhan Karunakaran; Thilahgavani Nagappan; Tengku Sifzizul Tengku Muhammad3; Sevakumaran Vigneswari (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2022)
Sea cucumber has long been utilized as a treatment for a variety of ailments, including antibacterial, antifungal, immunomodulatory, and wound healing. As for the first time, the extracts of three sea cucumber species’ i.e, Actinopyga lecanora, Holothuria atra, and Stichopus vastus, were compared and tested on the cytotoxicity of cancer cells using MTT and Annexin V/Propidium Iodide assays. This study investigates the protection of sea cucumber extracts against the breast cancer cell line (T-47D). All three extracts were found to be actively declining the cancer cell progression, with the IC50 values of 6.25±0.50 µg/ml (A. lecanora), 7.5 ± 1.39 µg/ml (H. atra) and 3.25 ± 0.53 µg/ml (S. vastus). LC-MS/MS analysis was used to identify chemical compunds in the extracts. The 1,1-diphenyl-2-picrylhydrazyl (DPPH), total phenolic and flavonoid contents, and anti-collagenase activity were also assessed in all the three extracts. The results demonstrated the absence of antioxidant and flavonoid chemicals in S. vastus, A. leconara and H. atra extracts. However, H. atra contained phenolic compounds (0.4794 mgGAE/g DW). Furthermore, all tested extracts showed significant anti-collagenase activity, which supported the reduction of cancer cell proliferation. However, more research into the mechanism of action of the extract is needed before sea cucumbers therapeutic characteristics may be used to combat breast cancer.